Figuring the Context of CTL under 2013 Curiculum - Chairina Nasir; Ika Apriani Fata; Bukhari Daud; Nia Isniati (Soegijapranata Catholic University, 2016)
The 2013 curriculum states that the purpose of teaching English for junior high school is to develop students’ communicative competence. In line with this expectation, several learning characteristics have been defined i.e. learning from model, observing, questioning, gathering information, associating, and communicating. Therefore, the teaching approaches that are used by the teacher in teaching English must suit the criteria to promote students' communicative competence. Contextual Teaching and learning (CTL) seems to be compatible as an approach since it has the the characteristics of constructivism, questioning, inquiry, learning community, modelling, reflection, and authentic assessment, which are similar to the learning characteristics mentioned above, which are similar to the learning characteristics mentioned above. , which are similar to the learning characteristics mentioned above. Therefore, a qualitative research concerning the issue was conducted to see how CTL approach is implemented under the 2013 curriculum in teaching reading comprehension. From the result of observation, questionnaire, and interview as the instruments, it was found that CTL was implemented properly from phase to phase and is applicable to be implemented under the curriculum. Also, it promotes active and enjoyable learning, facilitates the students to comprehend the material and helps them to implement the knowledge in real life. The. The teacher had implemented all of the procedures of CTL under the instruction of the 2013 curriculum. Thus, applying the CTL CTL approach in the process of teaching for the 2013 curriculum for the 2013 curriculum is recommended since it gives satisfactory benefits for students.